Traffic measurement and analysis of Wide Area Network (WAN) link usage: a case study of UiTM Perlis campus network / Abidah Mat Taib, Rafiza Ruslan and Abdul Hadi Kamel Abdullah - Mat Taib, Abidah; Ruslan, Rafiza; Abdullah, Abdul Hadi Kamel (Universiti Teknologi MARA, Perlis, 2010)
Network users normally will start complaining when the response time for the network access is intolerable or their network access is intermittently interrupted due to unclear reasons. Knowing how the network bandwidth is being utilized by the users will give the administrator some ideas of possible reasons for the network access problems and how to alleviate the problems. Some users may just use the network for running non bandwidth intensive applications like email and telnet and some users may use the network for running bandwidth intensive application such as video streaming and downloading big files using ftp application. Many users may visit popular web sites that are not related to their work during office hours. The above information about bandwidth utilization on a network link can be acquired through measurement and analysis of the network traffic that pass through the link. This paper discuss real time passive measurement of the network traffic on the WAN link that connects UiTM Perlis campus network to the main campus of UiTM in Shah Alam. The analysis of the traffic helped us to know some aspects of the WAN link utilization. This includes the average bandwidth utilization, popular application layer protocols and popular websites among different user segments and also some anomalies found in the captured traces